Program support matters: A systematic review on teacher- and school related contextual factors facilitating the implementation of social-emotional learning programs - Ulla, Triin; Poom-Valickis, Katrin (Frontiers in Education, 2023)
School- and teacher-related contextual factors are those that often influence the quality of social-emotional learning program implementation, which in turn has an impact on student outcomes. A systematic literature review was carried out to understand the diversity in school- and teacher-related contextual factors that influence the social-emotional learning (SEL) program implementation quality at school and to specify, which factors could be more pertinent for facilitating quality implementation. A search carried out in seven electronic databases resulted in an initial inclusion of 1281 records and additional journal and citation sampling of 19 records, from which 20 papers emerged that met the inclusion criteria (19 quantitative and one mixed methods). Thematic coding and quantitative analysis were employed to map the variables and estimate the relative frequency of statistically significant relationships across studies. Four categories of contextual factors were revealed: program support, school, teacher and student level. Types of factors demonstrating the most frequent statistical significance in studies were modeling activities during coaching and teacher-coach working relationship. Teacher burnout was uniquely related to program dosage. Student factors were the least studied contextual factors, but are shown as important for future consideration.